PEMBERDAYAAN EKONOMI PEREMPUAN DI DESA BANJARBENDO - Ari Yohanes Decaprio; Isna Fitria Agustina (Journal Publicuho, 2024)
Women's economic empowerment in Banjarbendo Village is one of the business alternatives where women participate in community life. As a village area in an urban area, the opportunity to improve the economy of the people of Banjarbendo Village is quite large in trade, culinary and MSMEs. Apart from that, agriculture and animal husbandry can still be developed even though land is decreasing. The research aims to identify women's economic empowerment through entrepreneurship in the context of economic growth which is expected to support the creation of a more sustainable and inclusive economic development strategy in Banjarbendo Village. This research is qualitative based on observation, interviews and documentation. The results illustrate that women's economic empowerment in Banjarbendo Village has not run as it should. Women's access to gender roles is limited, limiting their ability to engage in financially profitable activities, and women's control over their empowerment remains below standard.